A branch university journal as an information resource: the bibliometric analysis experience - G. I. Sbitneva (Библиосфера, 2019)
One of the most widespread publications of a university is «Vestnik» (Bulletin), which reflects not only scientific and professional interests of the university in a certain subject field, but scientific and professional interests of the scientific community within its territory and abroad. The journal testifies to the branch science development in general, contributes to formation of socio-economic and scientific environment of a certain region, and the country as a whole.  The article deals with the journal «Bulletin of Kemerovo State University of Culture and Arts» («Vestnik of KemGUKI») as an information resource of the branch university. The author studies main characteristics of the publication in the Russian Science Citation Index; concludes that the journal quality indicators (its index and place the Science Index rating, two-year and five-year impact factor) are constantly growing, that indicates promoting the publication in the professional community information environment. The paper highlights the bibliometric analysis results for 5 years (2013–2017) investigating publications (segments of document flow, micro-flows) grouped by features of content, species and author's structure.  The journal reflects a wide range of humanitarian knowledge. The authors of «Vestnik KemGUKI» are highly qualified teachers, their scientific and educational activities develop the branch science and professional education and form the University positive image. «Vestnik» is a platform to present and test dissertators’ re-searches. The document flow analysis on the authors’ affiliations allowed identifying teams that work in line with the interests of KemGUCA. Among them are not only universities of culture and other humanitarian educational institutions, but organizations not related to educational activities.  Studying the authors’ regional affiliation, the paper reflects the geographical landscape wideness. The authors are not only from Kemerovo, as well as from a large number of regional centers, cities and republics. Thanks to scientists and teachers of the neighboring countries (Ukraine, Belarus, Kazakhstan, Kyrgyzstan) the range of authors is constantly expanding. The study reveals coincidence of scholar interests with the scientific educational community of foreign countries (Poland, Bulgaria, Germany, China, India). It shows that «Vestnik» is recognized in the professional environment of the humanitarian community as a resource promoting education, science and culture in Kuzbass, Siberia, Russia, and the near and far abroad.